Dental Service Quality and Patient Satisfaction: Insights from Anutapura General Hospital, Palu City - Sudirman Sudirman; Herlina Yusuf; Nurhidayati Nurhidayati; Maya Ariandini (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: In line with Indonesia's healthcare development, this study investigates the impact of service quality dimensions on patient satisfaction in dental clinics at Anutapura General Hospital, Palu City. Emphasizing health as a fundamental human right, the research aligns with national objectives for comprehensive healthcare efforts. Method: Employing quantitative methods, data from 97 patients was collected through convenience sampling, focusing on dimensions including physical evidence, reliability, responsiveness, assurance, and empathy. Result: Analysis revealed significant correlations between these dimensions and patient satisfaction. Notably, patients perceiving good physical evidence and reliability reported higher satisfaction levels. However, responsiveness showed a positive trend without statistical significance. Assurance and empathy emerged as crucial determinants, significantly influencing patient satisfaction. These findings emphasize the importance of infrastructure investment, staff training, and patient-centered care approaches in enhancing service quality. Conclussion: The study underscores the need for continuous quality improvement efforts to achieve better healthcare outcomes in dental care settings. Prioritizing patient perspectives, fostering trust and empathy in patient-provider relationships, and sustaining quality enhancement initiatives are vital for advancing healthcare quality and patient satisfaction in Indonesia's evolving healthcare landscape.